2010
DOI: 10.1111/j.1467-8543.2009.00748.x
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating ‘Difference’: Representing Disabled Employees in the British Workplace

Abstract: Drawing on qualitative interviews with disabled employees, union officers and disability-related organizations, this article examines employee attempts to negotiate workplace adjustments and associated issues of workplace representation. UK employment law utilizes an individual medical model of disability, which conflicts with traditional collective approaches favoured by trade unions, which has implications for disabled employees and union representation. We explore the different strategies available to union… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 32 publications
2
70
0
2
Order By: Relevance
“…Such reticence and resistance is evidenced in recent research, in that many employers lack formal procedures concerning adjustments for disabled employees (Foster and Fosh, 2010). In further current research it has also been found that employers are all too often caught in the Employees with Asperger syndrome habit of designing jobs that make insufficient allowance for difference (Foster and Wass, 2011).…”
Section: Employees Withmentioning
confidence: 92%
“…Such reticence and resistance is evidenced in recent research, in that many employers lack formal procedures concerning adjustments for disabled employees (Foster and Fosh, 2010). In further current research it has also been found that employers are all too often caught in the Employees with Asperger syndrome habit of designing jobs that make insufficient allowance for difference (Foster and Wass, 2011).…”
Section: Employees Withmentioning
confidence: 92%
“…Debates on HRM have drawn upon a disability studies social model interpretation of disability to call for disability discrimination legislation (Barnes 1992) and an exploration of the impact of the Disability Discrimination Act (1995) upon employer practices (Woodhams and Corby 2007). Foster (2007) considered legal entitlement and disabled workers' negotiations for reasonable adjustments and later the role of union offices in enabling such negotiations (Foster and Fosh 2010). However, Riach and Loretto (2009) suggest the emphasis in employment-related studies remains an individual or medicalized understanding of disability.…”
Section: Disability In Hrm and Diversity Debatesmentioning
confidence: 99%
“…This approach often focuses on the identity of the individual or groups marked as 'different' and can be pursued through case studies or narratives (examples include Anitha et al, 2012;Foster and Fosh, 2010;Williams-Whitt and Taras, 2010;Hebson, 2009). Whilst all these studies are intersectionally-sensitive and provide us with new insights into the experience of these hitherto neglected groups of workers, a number of writers warn against the dangers of essentialism, such that these insights are taken as representative of all workers who might fall within the same intersectional categories (Choo and Ferree, 2010;Dhamoon, 2011;Yuval Davis, 2006).…”
Section: The Challenge Of Taking An Intersectional Approachmentioning
confidence: 99%